Parsimony and complexity in epidemiological models for decision support in animal health - Zagmutt, Francisco J., author; Dow, Steven W., advisor; Hill, Ashley, advisor; Webb, Colleen T., committee member; Wagner, Bruce A., committee member (Colorado State University. Libraries, 2012)
To view the abstract, please see the full text of the document.
Keywords: modeling; policy; risk analysis; simulation; SIR; stochastic